For Hunger-proof Cities: Sustainable Urban Food Systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
M Koc, R MacRae, L J A Mougeot, and J Welsh. IDRC. 1999. 300 pp.ISBN 0 88936 882 1$35.00 Euro 33.65IDRC,PO Box 8500, Ottawa, ON, Canada K1G 3H9Fax: + 1 613 563 2476Email: pub@idrc.ca